THE EFFECT OF SCARIFICATION TREATMENT AND SPROUT MEDIA ON NYAMPLUNG SEED GERMINATION (Calophyllum inophyllum L.) - Aluyah, Cik; Sosilawati, Endang; Hidayat, Agus Baktiawan (Sylva Jurnal Ilmu-ilmu Kehutanan, 2024)
Nyamplung (Calophyllum inophyllum L.) is one type of tropical forest plant that has high economic value, can be used as a plant that produces wood or non-wood. The constraints of nyamplung seedling efforts at the nursery level include having hard seeds that cause physical dormancy in the seeds. The purpose of this study was to determine the effect of scarification treatment and the composition of the germination media on the germination of nyamplung seeds This study was conducted in the Greenhouse and Laboratory of the Palembang Forestry Research Center, using an experimental method with a Factorial Completely Randomized Design consisting of two factors, namely seed scarification with 4 treatments and the composition of the germination media with 4 treatments. The results of the study showed that scarification by peeling the outer skin of the seeds and then soaking them in cold water for 24 hours gave the best effect on nyamplung seed germination, while the composition of the germination media and the interaction between the seed scarification treatment and the composition of the germination media had no significant effect on all parameters observed.